Cover Image, Volume 39, Issue 4. Issue 4 (6th March 2018) - Anand, Deepti; Agrawal, Smriti A.; Slavotinek, Anne; Lachke, Salil A.
Abstract : On the cover : This cover image, by Deepti Anand et al., is based on the article Mutation update of transcription factor genes FOXE3, HSF4, MAF, and PITX3 causing cataracts and other developmental ocular defects, Pages 471–494. DOI:10.1002/humu.23395 .